2017
DOI: 10.5137/1019-5149.jtn.20401-17.3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rosmarinus officinalis and chemotherapeutic etoposide on glioblastoma (u87 mg) cell culture

Abstract: Rosmarinus Officinalis offers hope for developing new cancer treatment strategies. However, further studies are needed to verify these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…According to previous study it was observed that while increased quantities of Rosmarinus Officinalis infusion solution induced MEF cell proliferation, it inhibited the survival of GBM cells in three and five days (48). In this study the same effect of Rosmarinus Officinalis infusion solution was observed in one day.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…According to previous study it was observed that while increased quantities of Rosmarinus Officinalis infusion solution induced MEF cell proliferation, it inhibited the survival of GBM cells in three and five days (48). In this study the same effect of Rosmarinus Officinalis infusion solution was observed in one day.…”
Section: Discussionsupporting
confidence: 80%
“…It was sterilized by 22 µM pore sized filter. From our previous studies 1/75 (v/v) rosemary has already been determined as optimum for both MEF and GBM cells (48). It is the dose which has minimum cytotoxic effect on the MEF cells and maximum cytotoxic effect on the GBM cells.…”
Section: Preparation Of the Rosmarinus Officinalis Infusion And Extraction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Campthothecin Inhibits PP1 and PP2 at serine/threonine phosphatases and cell growth inhibition 50 [129,130] Cycloheximide Inhibits p38 activated protein kinase (MAKPK) a nd cell entry at G2/M phase 5 [131,132] Etoposide Down regulate polymerase II at S-G2 phases and prevents cell division 50 [133,134] Ofloxacin 4-Fluorquinolone inhibits polymerase at G2/M phase, and apoptosis 30 [135,136] Praziquantel Isoquinolone inhibits serine/threonine kinase (PI3-k) polymerases I and II 46 [137][138][139] Staurosporine Protein kinases inhibitor (A, C, CAM and PI3K) prevents cell growth at G1 check point 9 [140,141] *Each drug suspension (µg/100 µL) in 0.15M NaCl used in the cytotoxic in vitro assays. µg…”
Section: Polymerase Inhibitorsmentioning
confidence: 99%
“…Moreover, RE by itself promoted the growth of Mouse Embryonic Fibroblast (MEF) cells, while reducing the negative impact of etoposide on these cells when employed simultaneously with etoposide. It can be presumed that RE protects healthy cells from the negative effects of etoposide, without reducing its action in GBM cells [130].…”
Section: Synergistic Action and Chemoadjuvant Effect Of Rosemarymentioning
confidence: 99%